2021
DOI: 10.3390/ijerph18041557
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome during Residency Training in Jordan: Prevalence, Risk Factors, and Implications

Abstract: Burnout syndrome is common among healthcare professions, including resident physicians. We aimed to assess the prevalence of burnout among resident physicians in Jordan, and a secondary aim was to evaluate the risk factors associated with the development of burnout syndrome in those residents, including gender, working hours, psychological distress, training sector, and specialty. In this cross-sectional study, 481 residents were recruited utilizing multistage stratified sampling to represent the four major he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
2
20
0
2
Order By: Relevance
“…JUH is the first and largest academic hospital in Jordan with a total of 600 beds [ 22 ]. In addition, it is the major referral center for all of central Jordan serving more than four million patients [ 23 ]. JUH treats more than half a million patients annually and conducts about 25,000 surgical operations every single year [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…JUH is the first and largest academic hospital in Jordan with a total of 600 beds [ 22 ]. In addition, it is the major referral center for all of central Jordan serving more than four million patients [ 23 ]. JUH treats more than half a million patients annually and conducts about 25,000 surgical operations every single year [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…17 Other studies found that medical residents tend to have the highest score of personal burnout rather than 2 other subscales, despite the burnout level. [17][18][19] These findings show us that medical residents have personal physical and psychological exhaustion that did not relate to their work.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it serves more than four million patients by being located in the center of Jordan [23]. JUH houses 600 beds and treats more than half a million patients annually while conducting about 20,000 surgical procedures every single year [24]. Recently, JUH installed its EMR system as an adjunct to the hospital's paper-based system from 2009 to present.…”
Section: Methodsmentioning
confidence: 99%